Silver fir and Douglas fir are more tolerant to extreme droughts than Norway spruce in south-western Germany - Vitali, Valentina; Büntgen, Ulf; Bauhus, Jürgen (Global change biology, 2017)
Improving our understanding of the potential of forest adaptation is an urgent task in the light of predicted climate change. Long-term alternatives for susceptible yet economically important tree species such as Norway spruce (Picea abies) are required, if the frequency and intensity of summer droughts will continue to increase. Although Silver fir (Abies alba) and Douglas fir (Pseudotsuga menziesii) have both been described as drought-tolerant species, our understanding of their growth responses to drought extremes is still limited. Here, we use a dendroecological approach to assess the resistance, resilience, and recovery of these important central Europe to conifer species the exceptional droughts in 1976 and 2003. A total of 270 trees per species were sampled in 18 managed mixed-species stands along an altitudinal gradient (400-1200 m a.s.l.) at the western slopes of the southern and central Black Forest in southwest Germany. While radial growth in all species responded similarly to the 1976 drought, Norway spruce was least resistant and resilient to the 2003 summer drought. Silver fir showed the overall highest resistance to drought, similarly to Douglas fir, which exhibited the widest growth rings. Silver fir trees from lower elevations were more drought prone than trees at higher elevations. Douglas fir and Norway spruce, however, revealed lower drought resilience at higher altitudes. Although the 1976 and 2003 drought extremes were quite different, Douglas fir maintained consistently the highest radial growth. Although our study did not examine population-level responses, it clearly indicates that Silver fir and Douglas fir are generally more resistant and resilient to previous drought extremes and are therefore suitable alternatives to Norway spruce; Silver fir more so at higher altitudes. Cultivating these species instead of Norway spruce will contribute to maintaining a high level of productivity across many Central European mountain forests under future climate change.
Keywords: jedle; Abies alba; Europe; Abies; Picea abies; Pseudotsuga; Norway; dendroecology; Norsko; klimatické změny; Pseudotsuga menziesii; Evropa; Adaptation, Physiological; Central Europe; Droughts; smrk; drought tolerance; lesy; fyziologická adaptace; Climate Change; Forests; Picea; Germany; forest management; období sucha; climate change; Německo